2013
DOI: 10.1155/2013/781084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low‐Level Autonomic Stimulation on Prevention of Atrial Fibrillation Induced by Acute Electrical Remodeling

Abstract: Background. Rapid atrial pacing (RAP) can induce electrical and autonomic remodeling and facilitate atrial fibrillation (AF). Recent reports showed that low-level vagosympathetic nerve stimulation (LLVNS) can suppress AF, as an antiarrhythmic effect. We hypothesized that LLVNS can reverse substrate heterogeneity induced by RAP. Methods and Results. Mongrel dogs were divided into (LLVNS+RAP) and RAP groups. Electrode catheters were sutured to multiple atrial sites, and LLVNS was applied to cervical vagosympathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Given that low-level vagus nerve stimulation has shown antiarrhythmic effects, 4 , 6 the possibility to reduce AF recurrence by parasympathetic stimulation using acupuncture in addition to antiarrhythmic drug therapy or ablation is a promising approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that low-level vagus nerve stimulation has shown antiarrhythmic effects, 4 , 6 the possibility to reduce AF recurrence by parasympathetic stimulation using acupuncture in addition to antiarrhythmic drug therapy or ablation is a promising approach.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Potential additional therapeutic approaches such as cardiac ganglionic ablation or denervation as well as noninvasive approaches via electroacupuncture have delivered promising results concerning a reduction of AF episodes. [4][5][6][7] In a canine model, low-level transcutaneous electrical stimu-lation-defined as stimulation at a voltage approximately 10% beneath the threshold of vagus nerve stimulation inducing any slowing of sinus rate or atrioventricular conduction-of the auricular branch of the vagus nerve (ABVN) showed antiarrhythmic effects by suppressing neural activity within the ganglionated plexi and thereby inhibiting inducibility of AF. 7 In patients with paroxysmal AF, low-level vagal stimulation recently demonstrated significant reduction in AF burden.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in HRV when stimulating heart auricular acupoint can be a potential approach in clinical practice. Previous studies have shown that stimulating the vagus nerve in the ear with an increase in HRV will have an antiarrhythmic effect, potentially reducing the recurrence of atrial fibrillation when combined with an antiarrhythmic drug [ 23 , 24 ]. Therefore, future studies to determine the influence of auricular acupuncture on heart acupoints in patients with atrial fibrillation are particularly promising.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several recent studies have demonstrated the ability of autonomic modulation to suppress and prevent AF in a variety of animal models [11][12][13][14], as well as in humans [15,16].…”
Section: Introductionmentioning
confidence: 99%